PENDAMPINGAN BANK SAMPAH YOGA MESARI DALAM PENINGKATAN PARTISIPASI MASYARAKAT MELALUI MEDIA BOOKLET - Suyasa, I Nyoman Gede; Rusminingsih, Ni Ketut (Poltekkes Kemenkes Denpasar, 2024)
Based on data from the Department of Environment and Parks, the amount of waste in Badung Regency is 250 tons per day, to deal with the waste problem, the Badung Regency Government is one of its efforts to establish a waste bank, currently there are only 125 waste banks. This waste bank was formed in the banjar, village to schools and private institutions. Waste production in Mengwi Village, Mengwi District, Badung Regency is 25 cubic feet per day, to handle this waste, one of the efforts is made by the Yoga Mesari waste bank, this waste bank serves a population of 7,602 people from 11 banjars in Mengwi Village with 2178 families.The priority problems that need to be solved are the level of community participation in the waste bank program is still lacking, the lack of waste sorting facilities and infrastructure in each household and the lack of weighing facilities in each householdThe method of service is by providing assistance to the community in the waste bank program. The measurement of the level of community participation was carried out before and after being given health education with the media booklet. This service activity is carried out within three months,The results of community service showed that there was an increase in community participation after assistance with booklet media in the good category from 35.50% to 49.50%. and the very good category from 21.50% to 44.00%.It is hoped that the management of the Yoga Mesari waste bank will continue to educate the public by using booklet media so that community participation continues to increase in the waste bank program and actively collects waste to members to provide better services.